When Psoriasis Is Not Psoriasis: Tinea Incognito Induced by Long-Term Steroid Abuse - Ersi Dwi Utami; Redha Cipta Utama (GoAcademica Research & Publishing, 2026)
Background: Tinea incognito is a dermatophyte infection with atypical clinical features caused by inappropriate use of topical or systemic corticosteroids. It often mimics other dermatoses, particularly psoriasis, leading to delayed diagnosis and inappropriate management. Misuse of steroids may mask inflammation while allowing fungal proliferation and dissemination. Case Presentation: A 60-year-old male farmer presented with a two-week history of pruritic, thick, scaly erythematous plaques involving the chest, abdomen, back, and upper arms, accompanied by fever, myalgia, and malaise. Initially, the patient noticed mildly pruritic erythematous patches one month prior and self-treated with topical dexamethasone, resulting in temporary relief but progressive worsening. He also reported long-term oral dexamethasone use (0.5 mg daily for 10 years). Lesions evolved into widespread plaques with thick scales and pustules, clinically resembling pustular psoriasis. KOH examination of skin scrapings revealed long septate hyphae, confirming dermatophytosis, while Gram staining was negative for bacteria. Laboratory findings were unremarkable. The diagnosis of extensive tinea incognito with concurrent viral infection was established. The patient was treated with oral itraconazole (200 mg/day) and topical ketoconazole for four weeks, showing significant clinical improvement by the third week. Conclusion: This case highlights the importance of considering tinea incognito in steroid-modified dermatoses mimicking psoriasis. Early mycological examination is essential to avoid misdiagnosis and inappropriate steroid use. Rational antifungal therapy leads to favorable outcomes. Keywords: tinea incognito; corticosteroid abuse; psoriasis mimicry; dermatophytosis